2018
DOI: 10.3892/or.2018.6741
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑424 serves an anti‑oncogenic role by targeting cyclin‑dependent kinase�1 in breast cancer cells

Abstract: The aim of the present study was to define the function of microRNA-424-5p (miR-424) in breast cancer cells. The present study investigated the level and the potential function of miR-424 in breast cancer by reverse transcription-quantitative polymerase chain reaction assays. miR-424 expression was decreased in the majority of human breast cancer specimens and cell lines used in the present study. The MTT assay, plate colony formation assay and flow cytometry analyses were used to characterize the function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…The findings of the above‐mentioned project showed that miR‐424‐5p can decrease cellular growth and arrest cancerous cells in the cell cycle through inversely modulating the CDK1 transcript in breast carcinoma, probably via the Hippo and the extracellular signal‐modulated kinase axis. These results provided new evidence confirming the function of miR‐424‐5p in BC (Xie et al, 2018). Different natural‐based molecules, including resveratrol, have been demonstrated to positively modulate microRNA level; this modulatory function is important in tumor prevention and therapy (Otsuka et al, 2018).…”
Section: Introductionsupporting
confidence: 69%
“…The findings of the above‐mentioned project showed that miR‐424‐5p can decrease cellular growth and arrest cancerous cells in the cell cycle through inversely modulating the CDK1 transcript in breast carcinoma, probably via the Hippo and the extracellular signal‐modulated kinase axis. These results provided new evidence confirming the function of miR‐424‐5p in BC (Xie et al, 2018). Different natural‐based molecules, including resveratrol, have been demonstrated to positively modulate microRNA level; this modulatory function is important in tumor prevention and therapy (Otsuka et al, 2018).…”
Section: Introductionsupporting
confidence: 69%
“…Studies found that multiple abnormally expressed miRNAs in BC directly target CDK and participate in the regulation of tumor progression. The expression of miR-424 is reduced in most human BC specimens and cell lines, and increased expression of miR-424 reduces the expression of CDK1, thereby causing G2/M cell-cycle arrest and inhibiting cell proliferation [167]. MiR-128-3p inhibits the proliferation and motility of BC cells by affecting the expression of CDK4/6/cyclin D1 and CDK2/cyclin E1, leading to G0/G1 phase arrest [168].…”
Section: The Novel Cdk Inhibitors In Bcmentioning
confidence: 99%
“…This study also showed that miR-424 gained its anti-oncogenic functions by binding to its selective target, cyclin-dependent kinase CDK1 . In addition, the expression of the Yes-associated protein YAP, of the Hippo pathway, and p-ERK1/2 of the ERK pathway were also decreased upon miR-424 overexpression [65]. Furthermore, another study by Chen et al provided evidence that miR-543 suppressed breast cancer cell proliferation, hindered cell cycling, and promoted cell apoptosis via direct regulating of ERK/MAPK pathway [66].…”
Section: Micrornas and The Hallmarks Of Breast Cancermentioning
confidence: 99%